miR-184, a downregulated ovary-elevated miRNA transcriptionally activated by SREBF2, exerts anti-apoptotic properties in ovarian granulosa cells through inducing SMAD3 expression - Baosen Shan; Yangan Huo; Zhennan Guo; Qiqi Li; Zengxiang Pan; Qifa Li; Xing Du (Cell Death and Disease)
Abstract Follicular atresia is the primary threat to female fertility. miRNAs are dysregulated in granulosa cells (GCs) during follicular atresia, and have emerged as crucial regulators of the initiation and progression of follicular atresia. However, the downregulated ovary-elevated (OE) miRNAs and their biological functions in ovary remain elusive. Here, 13 downregulated OE miRNAs were systematically identified by integrating tissue expression high-throughput data and comparative transcriptome analyses, among which miR-184 was specifically highly expressed in ovary but dramatically downregulated during follicular atresia. Low miR-184 levels were also positively correlated with follicular atresia. Based on the in vitro GC and follicle culture system, we found that miR-184 suppressed GC apoptosis and follicular atresia. Mechanistically, miR-184 induced SMAD3 transcription by acting as a saRNA, and also stabilized SMAD3 mRNA by directly binding to its 5′-UTR, which promoted TGF-β pathway activity and its anti-apoptotic effect. In addition, miR-184 was transcribed independently of host gene, which was activated by SREBF2 in an H3K4me3-dependent manner. Comparative analysis revealed that SREBF2 expression and H3K4me3 enrichment on miR-184 promoter in GCs from atretic follicles were dramatically reduced, which leads to the downregulation of miR-184 during follicular atresia. Moreover, the expression pattern, function, target, and regulatory mechanism of miR-184 among mammals are highly conserved and universal. Taken together, our findings demonstrate that miR-184, transcriptionally activated by SREBF2 in an H3K4me3-dependent manner, exerts anti-atretic effects by inducing SMAD3 expression, highlighting that it is a promising regulator for improving follicular development, ovarian health and female fertility.